Use of perioperative thermal camera for the assessment of sympathectomy effectiveness - Acıpayam, Ahmet; Yoldaş, Atila (The European Research Journal, 2024)
Objectives: Primary Hyperhidrosis (HH) is the excessive sweating condition in one or more parts of the body. The definitive treatment method is surgical. The most commonly applied surgical method is endoscopic thoracic sympathectomy (ETS). We aimed to investigate the effectiveness of patients with hyperhidrosis by making temperature measurements. Methods: We analyzed the findings of 30 patients who were diagnosed with HH between January 1, 2019 and November 1, 2022 in Kahramanmaraş Sütçü İmam University Thoracic Surgery Clinic. Preoperative, intraoperative and postoperative hand temperatures of the patients who underwent bilateral endoscopic thoracic sympathectomy were examined by measuring hand temperatures with a thermal camera. Results: After the evaluation of the examination, it was revealed that there was an increase in the hand temperature measurement values before sympathectomy and after the sympathectomy operation. Conclusion: We believe that endoscopic thoracic sympathectomy performed by measuring temperature with a thermal camera will increase the comfort and safety of the surgery both on the part of the physician and the patient.